Beverly B. Mack. Muslim Women Sing: Hausa Popular Song - Njoku, Obianuju Akunna (International Library of African Music, 2019)
pages: 159-163
Keywords: Women musicians; Popular music; Hausa (African people); Book reviews; Musicians; Muslim Women; Hausa Music; African Music